Amelanotic Melanoma: A Great Masquerader - Osama, Md Ali; Rao, Seema; Bakshi, Neha; Badwal, Sonia; Aggarwal, Shyam (Journal of Laboratory Physicians, 2022)
Malignant melanoma is an aggressive, notorious tumor showing great variability in morphological and immunohistochemical expression, thus commonly leading to an erroneous diagnosis. Within the melanoma group, amelanotic melanoma, with its wide clinical presentations, lack of pigmentation, and varied histological appearances, has taken on a new persona as a master masquerader. Use of immunohistochemistry in the diagnosis of malignant tumors, including melanoma, is primordial and indispensable. However, the problem gets compounded in scenario of aberrant antigenic expression. The present case posed multiple diagnostic challenges in form of atypical clinical presentation, variant morphology, as well as aberrant antigenic expression. Here, we present the case of a 72-year-old male who, upon his initial presentation, was thought to be sarcomatoid anaplastic plasmacytoma, but 5 months later another biopsy from a different site revealed the actual diagnosis of amelanotic melanoma.
Keywords: amelanotic; melanoma; plasmacytoma; plasma cell neoplasm; plasmacytoid; sarcomatoid